Research on risks faced by ADS-B system and solutions - SUN Baoming; CHEN Juan; GU Zhiming (Tongxin xuebao)
Due to its open technical system, ADS-B system was vulnerable to active jamming and deception, resulting in reduced performance. Aiming at this problem, the technical characteristics of ADS-B were analyzed, the possible jamming and detection risks faced by ADS-B system were elaborated, and the solutions of anti-interference and anti-deception were given.